Fetal subcutaneous tissue measurements in pregnancy as a predictor of neonatal total body composition. (9th June 2014) - O'Connor, Clare; Doolan, Anne; O'Higgins, Amy; Segurado, Ricardo; Sheridan‐Pereiraet, Margaret; Turner, Michael J.; Stuart, Bernard; Kennelly, Máireád M.
ABSTRACT Objective The purpose of this study was to examine the relationship between prenatal measures of subcutaneous tissue as surrogate markers of fetal nutritional status and correlate them with neonatal total body composition. Methods This prospective longitudinal study of 62 singleton pregnancies obtained serial biometry and subcutaneous tissue measurements at 28, 33 and 38 weeks gestation. These measurements were then correlated with neonatal body composition, which was analysed using the PEAPOD™ Infant Body Composition System (Cosmed USA, Concord, CA, USA). Results At 38 weeks gestation, fetal abdominal subcutaneous tissue (FAST) in millimetres was significantly associated with infant fat mass at delivery (+64 g per mm of FAST, p < 0.001). Thigh fat (TF) at 28 weeks gestation was associated with infant fat mass at delivery (+79 g/mm TF, p = 0.023). TF at 38 weeks gestation was associated with infant fat mass (+63/mm TF, p = 0.004). TF and FAST at 38 weeks were also predictive of both birth weight and increased abdominal circumference (AC) (p = 0.001) with FAST measurement predicting an additional 5.7 mm in AC per millimetre of FAST (p = 0.002) and TF predicting an additional 6.9 mm per mm of TF (p = 0.002). Conclusion We believe that this study further validates the use of prenatal measures of subcutaneous tissue and may help to highlight fetuses at risk of newborn adiposity and metabolic syndrome. © 2014 John Wiley & Sons, Ltd.